2020
DOI: 10.1017/s1047951120000104
|View full text |Cite
|
Sign up to set email alerts
|

Transcatheter closure of elongated and pulmonary hypertensive patent arterial duct in infants using Amplatzer vascular plug II

Abstract: AbstractObjective:To evaluate the feasibility, efficacy, and safety of Amplatzer vascular plug II in large and elongated ducts in infants.Introduction:Patent arterial duct device closure is technically challenging in infants with large and elongated ducts because Amplatzer duct occluder and Ampl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 18 publications
2
7
0
Order By: Relevance
“…In this multicenter experience, the offlabel utilization of such devices appears effective in children and infants (median age: 1 year). The overall rate of successful AVP implantation (98.5%) constitutes a major indicator of efficacy which compares favourably with previous reports on use of AVPs and other devices formally developed for PDA or vascular occlusions [1][2][4][5][6][7][8][9][10][11][12][13][14]21,[25][26][27][28][29].…”
Section: Discussionsupporting
confidence: 76%
See 4 more Smart Citations
“…In this multicenter experience, the offlabel utilization of such devices appears effective in children and infants (median age: 1 year). The overall rate of successful AVP implantation (98.5%) constitutes a major indicator of efficacy which compares favourably with previous reports on use of AVPs and other devices formally developed for PDA or vascular occlusions [1][2][4][5][6][7][8][9][10][11][12][13][14]21,[25][26][27][28][29].…”
Section: Discussionsupporting
confidence: 76%
“…Pertaining to the safety of "off-label" AVP use, we did not experience any major complications using AVP IV, as reported by several authors [1,17,21]. Interestingly, all MAE in our study solely involved PDA closure with AVP II in symptomatic infants ≤5 kg, well identified as being at higher risk during interventional cardiac catheterization [27,30]. On the other hand, this study also brings to light that AVP II remains a suitable alternative for the closure of very large PDAs in symptomatic infants weighing 2 to 6 kg, in whom the deployment of labelled devices might be impossible or at high risk of complications.…”
Section: Discussionsupporting
confidence: 69%
See 3 more Smart Citations